2014
DOI: 10.1002/mus.24332
|View full text |Cite
|
Sign up to set email alerts
|

Ataluren treatment of patients with nonsense mutation dystrophinopathy

Abstract: Introduction: Dystrophinopathy is a rare, severe muscle disorder, and nonsense mutations are found in 13% of cases. Ataluren was developed to enable ribosomal readthrough of premature stop codons in nonsense mutation (nm) genetic disorders. Methods: Randomized, double-blind, placebo-controlled study; males ≥5 years with nm-dystrophinopathy received study drug orally 3 times daily, ataluren 10, 10, 20 mg/kg (N = 57); ataluren 20, 20, 40 mg/kg (N = 60); or placebo (N = 57) for 48 weeks. The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
303
0
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(325 citation statements)
references
References 55 publications
7
303
0
15
Order By: Relevance
“…1 and SI Appendix, Fig. S3) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23); (ii) the effects on luciferase activity could not be independently replicated by others (24) or by us (SI Appendix , Fig. S3C); (iii) ataluren's putative luciferase inhibitory activity depends on a specific enzyme substrate (25); and (iv) most of the hypothetical inhibitory molecule, PTC124-AMP (22), is rapidly converted to the active readthrough molecule PTC124 (ataluren) under conditions of in vitro translation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and SI Appendix, Fig. S3) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23); (ii) the effects on luciferase activity could not be independently replicated by others (24) or by us (SI Appendix , Fig. S3C); (iii) ataluren's putative luciferase inhibitory activity depends on a specific enzyme substrate (25); and (iv) most of the hypothetical inhibitory molecule, PTC124-AMP (22), is rapidly converted to the active readthrough molecule PTC124 (ataluren) under conditions of in vitro translation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple experimental approaches with cell lines, patient cells, animal models, and genetic disorder patients have demonstrated that the drug ataluren can restore expression to genes and mRNAs otherwise inactive because of the presence of premature nonsense codons (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23). Collectively, such experiments have strongly suggested that ataluren promotes nonsense suppression, i.e., the insertion of near-cognate tRNAs at PTCs, but direct evidence for this activity has been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 3 trial of ataluren has been completed, but the results were not published at the time of our search. Results of a phase 2 have been published 59 . Ataluren received conditional marketing authorization from the European Commission to treat ambulatory DMD patients, aged five years and older with DMD nonsense mutation, considering its risk-benefit ratio 60 .…”
Section: Read-through Agentmentioning
confidence: 99%
“…Aujourd'hui, les maladies rares ont été repositionnées au coeur des préoccupations, avec d'importants programmes de recherche initiés et financés par des institutions publiques au niveau transnational. Plus déterminant encore, les progrès de la thérapie génique et de la pharmacogénétique sont sur le point, si ce n'est déjà fait, de révolu-tionner l'impact de ces maladies sur la vie des patients (Muntoni et Wood 2011 ;Cirak et al 2011 ;Arechavala-Gomeza et al 2012 ;Erriquez et al 2013 ;Scotter et Shaw 2013 ;Douglas et Wood 2013 ;Mercuri et Muntoni 2013 ;Touznik et al 2014 ;Bushby et al 2014 ;Voit et al 2014 ;Buyse et al 2015 ;Blat et Blat 2015). Suite à ces innovations thérapeutiques, de nouveaux besoins ont rapidement émergé, dont la nécessité de contrôler l'effet des traitements sur les muscles au cours du temps.…”
unclassified